Pembinaan Nilai-Nilai Religius Pada Peserta Didik Sdit Takwa Cendekia Makassar - Muhammad Arfandi Rauf; Bunyamin, Andi; Syahid, Akhmad (Program Pascasarjana Universitas Muslim Indonesia, 2023)
This research was conducted with the aim of describing how the teacher's strategy cultivated religious values in the students of SDIT Takwa Cendekia Makassar. This research uses a qualitative research approach. The informants consist of principals and PAI teachers, vice principals and homeroom teachers, and school operators. The method of data collection is done by observation, interviews, and documentation. The data collected from these techniques was analyzed using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the teacher's strategy for fostering religious values for students at SDIT Takwa Cendekia Makassar is to do program planning, set an example for students at school, partner with and contribute to encouraging religious activities, and carry out evaluations. Thus, it can be concluded that in fostering religious values, this is in accordance with what is desired by the school by looking at the process of fostering religious values using a fairly good strategy and getting a good response from all schools.